Salivary Gland Disorders - Myers, Eugene N.; Ferris, Robert L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Management of salivary disorders encompasses a broad array of diseases, both benign and malignant. To better demonstrate the evolution of this field and its diagnostic and therapeutic management, the contents of this book have been organized to reflect the diverse nature of salivary gland anatomy, physiology, and dysfunction in various states of disease. This text first addresses practical office-based diagnostic approaches. It continues with congenital and acquired salivary dysfunction, including the goals for restoration of gland function. The third portion of this book provides detailed information on assessment and therapy for benign and malignant tumors of the major and minor salivary glands. Each chapter is authored by internationally known authorities in this field. Illustrative photographs and sketches are included in each chapter, to demonstrate the disorders and surgical techniques described. In summary, this comprehensive book serves as a useful reference and practical manual for clinicians dealing with salivary gland disorders. Whether as an introductory or advanced reference text, the reader will find that this book fulfills an important role in the management of salivary gland diseases.
Anatomy, Function, and Evaluation of the Salivary Glands -- Imaging of the Salivary Glands -- Pathology of Salivary Gland Disease -- Biopsy of Minor Salivary Glands of the Lip -- Treatment of Frey’s Syndrome -- Sialendoscopy -- Removal of Calculi or Strictures in Salivary Ducts that Cannot be Removed by Sialendoscopy -- Fine-needle Aspiration Biopsy -- Management of Infections of the Salivary Glands -- Management of Mucocele and Ranula -- Xerostomia -- Diagnosis and Management of Autoimmune Salivary Gland Disorders -- Disorders of the Salivary Glands in Children -- Superficial Parotidectomy -- Total Parotidectomy -- Recurrent Pleomorphic Adenoma -- Management of the Mass in the Buccal Space -- Management of the Mass in the Prestyloid Parapharyngeal Space -- Vascular Lesions of Salivary Glands -- Tumors of Minor Salivary Gland Origin -- Management of Tumors of the Submandibular and Sublingual Glands -- Management of Cancer Metastatic to the Parotid Gland -- Temporal Bone Resection -- Facial Nerve Reconstruction -- Management of the Neck in Cancer of the Salivary Glands -- Reconstruction After Excision of Cancer of the Salivary Glands -- Role of Radiotherapy in the Treatment of Tumors of the Salivary Glands -- Chemotherapy in the Management of Malignant Tumors of Salivary Gland Origin -- Quality of Life in Patients with Disease and Tumors of Salivary Gland Origin.
Keywords: Otorhinolaryngology; Oral surgery; Maxillofacial surgery; Otorhinolaryngology; Oral and Maxillofacial Surgery